Pengembangan Media Puzzle Terhadap Pemahaman Materi Pecahan Pada Peserta Didik - Irmayanti, Irmayanti; Yandari, Indhira Asih Vivi; Fajrudin, Lili (Jurnal Gentala Pendidikan Dasar, 2026)
Some fourth-grade elementary school students have significant difficulty in understanding the concept of fractions, including distinguishing between numerators and denominators. The limitations of innovative learning media and minimal school facilities, combined with monotonous teaching methods, result in low interest and mathematics learning outcomes. This study aims to identify the development process of puzzle media for fractions, determine the feasibility of the developed puzzle media and analyze students responses after using puzzle media in fractional learning. This research uses a Research and Development (R&D) approach with ADDIE (Analysis, Design, Development, Implementation, Evaluation). The results of the study showed that puzzle media was effective in improving students understanding of fraction concepts and learning interests and puzzle larning media proved to be an effective solution to overcome difficulties in understanding fractional concepts for fourth-grade elementary school students.